An unexpected discovery: the first species of Paraneseuthia Franz from the Mascarene Islands (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2025)
Paraneseuthia disjuncta sp. nov. is described, based on a male collected in Île aux Aigrettes, a small island off the south-east coast of Mauritius. Females of unknown species are also recorded from Réunion. This is the first record of this genus outside Eurasia and Australia-Oceania, greatly extending the known range of Paraneseuthia. World checklist of Paraneseuthia is given, and a distribution map of nominal species is presented.